Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10072-006-0524-z
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent cerebrovascular ischaemic events in patients with interatrial septal abnormalities: a follow-up study

Abstract: The aim of this study was to evaluate the risk of recurrent ischaemic cerebrovascular events (stroke or transient ischaemic attack (TIA)) in patients with patent foramen ovale (PFO) or atrial septal aneurysm (ASA) treated with different therapeutic regimens. We enrolled 86 patients aged 18-60 years with an unexplained ischaemic stroke or TIA referred to our inpatient department in the period May 1994-December 1999. Follow-up lasted until April 2003. Patients were excluded if the stroke or TIA was related to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Of these, 10 studies with 1,886 patients reported comparison of the 2 treatment modalities and were included for pooled comparative analysis (10,14,18,20,22,23,31,37,41,42). The distribution of patients in different study groups, along with their baseline characteristics, is demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 10 studies with 1,886 patients reported comparison of the 2 treatment modalities and were included for pooled comparative analysis (10,14,18,20,22,23,31,37,41,42). The distribution of patients in different study groups, along with their baseline characteristics, is demonstrated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…However, in subgroup analysis, TCD studies suggest a higher risk of recurrent cryptogenic stroke/TIA in patients with moderate or large RLS compared with those with small RLS (RR=2.91; 95% CI=1. 32 Figure 4B). No substantial heterogeneity was found in the analyses (combined outcome recurrent stroke/ …”
Section: Overall and Subgroup Analysesmentioning
confidence: 95%
“…Potentially eligible studies for the meta-analysis (n=21) were retained, after screening both the titles and abstracts of all studies. After retrieving the full-text version of the aforementioned 21 studies, 5 studies were excluded because the end points of medically treated patients were mixed with the end points of surgically treated (with percutaneous or open closure) patients, [26][27][28][29][30] 2 studies because of the absence of comparison group (patients without PFO or no shunt stratification) 31,32 and 1 study because the reported end point was the combined outcome of stroke, TIA, or death. 33 The remaining 13 studies 24,[34][35][36][37][38][39][40][41][42][43][44][45] and the available data from our study cohort were included both in the qualitative and quantitative synthesis, according to the presence of PFO (PFO present, PFO absent), the shunt size (small right-to-left shunt [RLS] versus moderate or large RLS, small or moderate RLS versus large RLS), and the available outcome data (stroke or TIA, stroke; Figure 1).…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Two studies suggest that the annual rate of recurrence is about four times that in patients with PFO alone 57 61. However, four other studies have failed to replicate this finding, and instead suggest that the presence of an ASA has little or no impact on the risk of recurrence 55 56 60 62. Contrary to previous belief, recent studies have also failed to find an association between the size of the PFO and the risk of recurrence 56 57 60.…”
Section: Patent Foramen Ovalementioning
confidence: 97%